2015
DOI: 10.1159/000369024
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Testosterone Is Consistently and Positively Associated with Extraversion: Results from The Netherlands Study of Depression and Anxiety

Abstract: Background: Testosterone has been postulated as a ‘social' hormone, but the relationship between testosterone and personality traits linked with socially oriented behaviors such as extraversion remains unclear. The objective of our study was to investigate the association between baseline salivary testosterone levels and the Big Five personality traits. Methods: We studied the relationship between salivary testosterone (morning and evening) and NEO-FFI (Five-Factor Inventory) personality traits in 1,611 partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 46 publications
2
26
1
1
Order By: Relevance
“…Conversely, increased blood flow through cerebellar tissue and higher levels of coherent activity in the cerebellum have been found to positively correlate to novelty seeking, positive affect and approachrelated behaviour (O'Gorman et al, 2006;Wei et al, 2011). The latter features are typical of an extraverted personality style and linked to higher endogenous levels of testosterone (Eysenk, 1967;Smeets-Janssen et al, 2015). Extraversion is negatively correlated with symptoms of depression and anxiety (Jylhä and Isometsä, 2006), and the risk of mood disorders is significantly higher in individuals who score low on extraversion and high on neuroticism (Grav et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, increased blood flow through cerebellar tissue and higher levels of coherent activity in the cerebellum have been found to positively correlate to novelty seeking, positive affect and approachrelated behaviour (O'Gorman et al, 2006;Wei et al, 2011). The latter features are typical of an extraverted personality style and linked to higher endogenous levels of testosterone (Eysenk, 1967;Smeets-Janssen et al, 2015). Extraversion is negatively correlated with symptoms of depression and anxiety (Jylhä and Isometsä, 2006), and the risk of mood disorders is significantly higher in individuals who score low on extraversion and high on neuroticism (Grav et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…However, basal testosterone levels were found to be decreased in female patients with SAD . Also, in relation to personality constructs relevant to social anxiety, testosterone was associated with higher extraversion, and lower neuroticism . Interestingly, in patients with SAD, high cortisol responses to the Trier Social Stress Test were associated with increased social avoidance tendencies on a social approach‐avoidance (AA) task when people make approaching and avoiding movements (often by pulling or pushing a joystick) in response to angry and happy faces.…”
Section: The Emotion Networkmentioning
confidence: 99%
“…Also of note, increased libido is only one possible mechanistic explanation for the link between T and sexual language. For example, men with elevated T may have also varied on mood (Amanatkar, Chibnall, Seo, Manepalli, & Grossberg, 2014), general motivation (Aarts & van Honk, 2009) or reward processing (Hermans et al, 2010), or other personality factors (Smeets-Janssen et al, 2015), all of which have been shown to be influenced by T and that may in turn increase sexual language with the partner. Nor can we rule out the possibility that men who use more sexually explicit language with their partner experience an increase in T, an interpretation that would be consistent with studies showing that visual (for example, Robin S Edelstein et al, 2011) and olfactory (Miller & Maner, 2010) sexual stimuli increase T levels.…”
Section: Discussionmentioning
confidence: 99%